THU0091 Tie2 induces an inflammatory phenotype in rheumatoid arthritis and psoriatic arthritis patients driven by angiopoietin-2. (12th June 2018) - García Pérez, S.; Kabala, P.A.; Malvar Fernández, B.; Tang, M.W.; Hartgring, S.A.; Conde, C.; Sleeman, M.; Baeten, D.L.; Tak, P.P.; Connor, J.; Reedquist, K.A.; Radstake, T.R.
Abstract : Background: Several studies have shown that angiopoietin signalling to Tie2 may play a role in the initiation and perpetuation of disease rheumatoid arthritis (RA) and psoriatic arthritis (PsA). However, the cell type(s) involved in this process, as well the specific role of Tie2 signalling in the synovium of arthritis patients, remain unclear. Objectives: To examine the role Tie2 signalling in macrophages and fibroblast-like synoviocytes (FLS) within the context of the synovial microenvironment of arthritic patients. Methods: Peripheral blood (PB) monocytes from healthy donors (HD) were differentiated with synovial fluid (SF) of RA and PsA patients. PB and SF monocytes from RA and PsA patients were differentiated into pro-inflammatory macrophages with IFN-γ. Tie2 expression was analysed by flow cytometry and quantitative PCR. Macrophages, RA FLS and synovial tissue explants were stimulated with Ang-1 or Ang-2 (200 ng/ml) alone or in combination with TNF (10 ng/ml) for 4 hour or 24 hour. mRNA and protein expression of inflammatory mediators was analysed by quantitative PCR and ELISA and luminex, respectively. Arthritis was induced in wild type (WT) and Tie2 over-expressing (Tie2-TG) mice by intraperitoneal injection of 100 ml of K/BxN serum on day 0 and day 2. Mice were sacrificed on day 14 after serum transfer. Results: Tie2 expression was observed IFN-γ-differentiated macrophages, from RA and PsA patients, as well as HD macrophages differentiated with RA and PsA SF. In all cases, both Ang-1 and Ang-2 stimulation significantly enhanced TNF-induced expression of pro-inflammatory cytokines (IL-6, IL-12B) and chemokines (IL-8, CCL-3 and CXCL-6). Tie2 activation also enhanced TNF-mediated production of these inflammatory mediators in RA FLS. The clinical severity of serum-induced arthritis was significantly higher in Tie2-TG mice compared to WT mice, associated with enhanced synovial expression of IL-6, IL12B, iNOS, CCL-2 and CXCL-10. Finally, we found that Ang-2, and to a lower extent Ang-1, induced the production of IL-6, IL-12B, IL-8, and CCL-3 in the synovial tissue explants of RA and PsA patients. Importantly, Ang-2 blockade with a specific neutralising anti-Ang2 antibody suppressed the production of IL-6 and IL-8 in synovial tissue of RA patients. Conclusions: These results suggest that Tie2 signalling, even within the complex microenvironment of affected synovial tissue, has an important pro-inflammatory role in the pathology of RA and PsA. As this effect can be reversed by Ang-2 neutralisation, interfering with Tie2 activity may be a promising therapeutic target in arthritic diseases. Disclosure of Interest: S. García Pérez: None declared, P. A. Kabala: None declared, B. Malvar Fernández: None declared, M. W. Tang: None declared, S. A. Hartgring: None declared, C. Conde: None declared, M. Sleeman Employee of: Formerly an employee at MedImmune for the duration of this collaboration, D. L. Baeten: None declared, P. P. Tak: None declared, J. Connor Employee of: MedImmune LCC, K. A. Reedquist: None declared, T. R. Radstake: None declared